Employee motivation, job satisfaction, customer satisfaction, and firm performance: the moderating role of employee empowerment - Makhamreh, Hebah Zaki; Alsakarneh, Asaad; Eneizan, Bilal; Ngah, Abdul Hafaz (Business: Theory and Practice, 2022)
This study mainly focuses on examining the effects of employee motivation on Job Satisfaction, job satisfaction on customer satisfaction, customer satisfaction on firm performance, and the moderating role of employee empowerment on the relationship between employee motivation and job satisfaction. The current study follows convenience sampling to collect the data. The questionnaire uses the survey method of self-administered. To analyse the relationship between the variable and test the hypothesis PLS3 (Partial least-squares) equation is used. The main contributors to the current study were staff of the hotels. The sample size of the study is 380 worker staff of a hotel. The findings of the study indicated that employee motivation effect significantly and positively on job satisfaction, job satisfaction effect significantly and positively on customer satisfaction, customer satisfaction effect significantly and positively on firm performance, and for the moderation the finding shows that Employee empowerment effect positively and significantly on the relationship between Employee motivation and Job Satisfaction.